Pemberdayaan Bagi Guru Dalam Membuat Educandy Untuk Asesmen Diagnostik Siswa - Nurzengky Ibrahim; Desy Safitri; Sujarwo; Arita Marini; Iqbal Pratama; Lutfia Alfityanti (Jurnal Ragam Pengabdian, 2025)
Technological developments have penetrated various aspects of life, including education and learning. The development of digital technology can be utilized to facilitate teachers in the learning process and learning assessment. Therefore, teachers need to adapt and improve literacy in utilizing technology for learning purposes in the digital age. Activities that can guide teachers in improving these competencies are needed through community service activities. This community service activity aims to empower teachers in designing and using Educandy as an interactive and effective diagnostic assessment medium to evaluate students' initial understanding. Through this empowerment activity, teachers are introduced to the concept of diagnostic assessment and the technical steps for creating game-based quizzes through the Educandy platform. The method used is providing training and guidance to teachers at SMP Negeri 2 Jakarta. The results of this empowerment activity not only improve teachers' digital literacy but also encourage innovation in learning strategies that are adaptive to students' needs and increase student interest in participating in learning evaluations through a fun approach.